Sources of the legitimacy of Vladimir Putin’s power in today’s Russia - Olga Nadskakuła-Kaczmarczyk (Ksiegarnia Akademicka Publishing, 2021)
The aim of this article is to present the legitimacy of power in Russia. The special emphasis is placed on the correlations between Russian political culture and the legitimacy of the power of Vladimir Putin. Taking into consideration that social acceptance and support given to the authorities are the result of the relationship between the values pursued by the government and the values recognized by the society, the author presents the example of this mechanism in Russia. As many theorists note, investigation of the degree of legitimacy of the authorities should be determined by the compatibility of arguments that are used by the rulers and values and attitudes approved by the society. Therefore, this paper will present the relations between the authorities and society as well as the perception of Vladimir Putin’s domestic and foreign policy by residents of the Russian Federation.